2023
DOI: 10.1001/jamainternmed.2023.0898
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Prescription Drug and Health Care Use Over 9 Years After the Large Drug Price Increase for Colchicine

Abstract: ImportancePrescription drug prices are a leading concern among patients and policy makers. There have been large and sharp price increases for some drugs, but the long-term implications of large drug price increases remain poorly understood.ObjectiveTo examine the association of the large 2010 price increase in colchicine, a common treatment for gout, with long-term changes in colchicine use, substitution with other drugs, and health care use.Design, Setting, and ParticipantsThis retrospective cohort study exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…1 A recent study by Ly et al revealed that emergency department visits and rheumatology consultations for gout increased by 39.8% and 10.5%, respectively, in 2019 compared with 2007, suggesting a potential deterioration in disease control subsequent to the Colcrys approval. 2 The pharmaceutical industry provides lectures, payments, educational materials, and meals to physicians as part of marketing their products in the United States. [3][4][5][6][7][8][9][10] Studies have demonstrated that these payments can alter prescribing behaviors, such as the use of repository corticotropin in preference to other corticosteroids.…”
Section: Introductionmentioning
confidence: 99%
“…1 A recent study by Ly et al revealed that emergency department visits and rheumatology consultations for gout increased by 39.8% and 10.5%, respectively, in 2019 compared with 2007, suggesting a potential deterioration in disease control subsequent to the Colcrys approval. 2 The pharmaceutical industry provides lectures, payments, educational materials, and meals to physicians as part of marketing their products in the United States. [3][4][5][6][7][8][9][10] Studies have demonstrated that these payments can alter prescribing behaviors, such as the use of repository corticotropin in preference to other corticosteroids.…”
Section: Introductionmentioning
confidence: 99%